2021
DOI: 10.4081/gc.2021.9470
|View full text |Cite
|
Sign up to set email alerts
|

Participatory community-based arts for older people living with dementia in the community: how are they evaluated? A scoping review

Abstract: Although the interests in participative arts for people living with a dementia has increased over the last decade, what is yet to be reviewed is how participatory community- based arts activities for this group of people are evaluated. The overall aim of the following scoping review is to understand the scope of measurement/evaluation methods/approaches used in studies that recruited participants with dementia from the community (not from health/clinical or residential aged care settings or nursing homes) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…40 The context where the person lives is also important; creating environments that maximize opportunities for participation has been the focus of hospital-based research, 36,41 while methods to involve people living in care homes also pose distinct challenges. 32,33 Creative methods have been proposed in earlier reviews, 15,16 and our review found two particular examples of group work using creative methods, 25,28 bearing out the potential of this approach. However, other approaches, such as education interventions, are also another way of providing the tools to promote inclusion and dementia friendly outcomes as was argued by Hebert and Scales.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…40 The context where the person lives is also important; creating environments that maximize opportunities for participation has been the focus of hospital-based research, 36,41 while methods to involve people living in care homes also pose distinct challenges. 32,33 Creative methods have been proposed in earlier reviews, 15,16 and our review found two particular examples of group work using creative methods, 25,28 bearing out the potential of this approach. However, other approaches, such as education interventions, are also another way of providing the tools to promote inclusion and dementia friendly outcomes as was argued by Hebert and Scales.…”
Section: Discussionmentioning
confidence: 88%
“…Creative methods have been proposed in earlier reviews, 15 , 16 and our review found two particular examples of group work using creative methods, 25 , 28 bearing out the potential of this approach. However, other approaches, such as education interventions, are also another way of providing the tools to promote inclusion and dementia friendly outcomes as was argued by Hebert and Scales.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation